Pelatihan Drama dalam Meningkatkan Karakter Moralitas Mahasiswa Semester 4 STKIP DARUSSALLAM - Na’imul Faizah; Lutfi Eskawati (Jurnal Pengabdian Masyarakat Nusantara, 2021)
Character education strengthening occurs not only theoretically in the classroom but also through habituation in daily life. Using drama as a method for character education can be effective because drama is closely linked to character development. This article aims to discuss the affirmation of drama appreciation learning in relation to the importance of character education for fourth-semester students at STKIP Darussalam Cilacap. The researcher applies a literature review methodology, focusing on the use of texts and library literature as primary sources. The results indicate that regular drama appreciation learning activities have a positive impact on students' development. The findings highlight the significant contribution of drama appreciation learning to character education at STKIP Darussalam. It teaches students moral values, ethics, and responsibilities. Additionally, interaction during drama activities plays a key role in enhancing students' tolerance towards differing opinions, backgrounds, and cultures, creating a holistic educational environment. The presence of drama as an art form, both at the elementary school level and as part of higher education curricula, should impact by reflecting the reinforcement of character education in the digital era, which increasingly overlooks essential foundational aspects of life, such as efforts to build good personal and moral character.